THE MORPHOSYNTACTIC STRUCTURE AMONG ISLAMIC BOARDING SCHOOL MULTILINGUAL STUDENTS IN INDONESIA: A LANGUAGE TRANSFER PHENOMENON - Yani, Achmad; Zen, Evynurul Laily; Suharyadi, Suharyadi (Journal of English Educational Study (JEES), 2024)
This study investigates the phenomenon of language transfer among multilingual students at an Islamic boarding school, focusing on the morphosyntactic structures in recount texts written by students. Using descriptive quantitative methods, the research was conducted at a boarding school in South Kalimantan. Data were collected through free-writing exercises with ten selected students. The findings showed no significant statistical difference in language transfer between English and Arabic. However, interviews indicated that students often use Indonesian when forming sentences in English and Arabic, supporting the TPM theory. Future research should include a larger sample size, particularly from boarding schools, as each institution’s unique approach to multilingual education can influence language transfer in different ways.